2018
DOI: 10.3390/catal8080301
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Heteroatom-Doped Nanocarbon for Metal-Free Oxygen Reduction Electrocatalysis: A Review

Abstract: Abstract:The oxygen reduction reaction (ORR) at the cathode is a fundamental process and functions a pivotal role in fuel cells and metal-air batteries. However, the electrochemical performance of these technologies has been still challenged by the high cost, scarcity, and insufficient durability of the traditional Pt-based ORR electrocatalysts. Heteroatom-doped nanocarbon electrocatalysts with competitive activity, enhanced durability, and acceptable cost, have recently attracted increasing interest and hold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 137 publications
0
26
0
Order By: Relevance
“…Therefore, for cost and stability reasons, new catalysts for the ORR are highly sought after. Attention in recent years has focused on transition metal active centers in carbon matrices, especially where the carbon is doped with heteroatoms such as nitrogen, though the presence of metal in these materials leads to significant durability challenges, again, particularly in acidic media, and so a new class of entirely metal‐free ORR catalysts has emerged in recent years as cost effective, durable, and electrochemically selective alternatives to traditional materials …”
Section: D Carbons For the Orrmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, for cost and stability reasons, new catalysts for the ORR are highly sought after. Attention in recent years has focused on transition metal active centers in carbon matrices, especially where the carbon is doped with heteroatoms such as nitrogen, though the presence of metal in these materials leads to significant durability challenges, again, particularly in acidic media, and so a new class of entirely metal‐free ORR catalysts has emerged in recent years as cost effective, durable, and electrochemically selective alternatives to traditional materials …”
Section: D Carbons For the Orrmentioning
confidence: 99%
“…Additionally, 1D or 2D catalysts can be difficult to process into working electrodes and may suffer from a lack of mechanical robustness or re‐staking of nanomaterials. Therefore, 3D carbon structures including varying porosity have recently been seen as routes to scalable, high‐performance electrodes for the ORR, including the possibility of free‐standing electrodes . Such is the interest in the field of heteroatom‐doped carbons for metal‐free ORR catalysts, the number of publications is rapidly increasing year on year.…”
Section: D Carbons For the Orrmentioning
confidence: 99%
See 1 more Smart Citation
“…Stevenson et al 53 proved in ORR the O 2 in a 2-electron path is reduced to form OOH on carbon nanotubes. Hu and Xiong et al 54,55 conrmed that nitrogen and boron-doped nanostructures as ORR catalysts have low price, great durability and excellent potential. Zhao and Wei et al 56,57 conrmed the doping of carbon nanotubes have vital roles on performance of ORR.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, one review paper and five research articles pay special attention to ORR high-performance electrocatalysts. For example, Xiong et al [9] summed up recent progress on three-dimensional hetero-atom-doped nanocarbon for metal-free ORR electrocatalysis; Schardt et al [10] carefully investigated the influence of the structure-forming agent on the composition, morphology and ORR performance of Fe-N-C electrocatalysts; Zhu et al [11] developed a novel metal-organic framework route to embed Co nanoparticles into multi-walled carbon nanotubes for ORR in alkaline media; Liu et al [12] fabricated N,S co-doped carbon nanofibers derived from bacterial cellulose/poly(methylene blue) hybrid for ORR; Liu et al[13] prepared porous Fe-N-S/C electrocatalysts for ORR in a Zn-air battery using g-C 3 N 4 and 2,4,6-tri(2-pyridyl)-1,3,5-triazine as binary nitrogen precursors; Zeng et al [14] reported the Ag 4 Bi 2 O 5 /MnO 2 corn/cob-like nanomaterial as a superior catalyst for ORR in alkaline media. One review paper and one research article are involved in the OER electrocatalysts.…”
mentioning
confidence: 99%